Community and household shocks and coping strategies: Findings from the eighth round of the Myanmar Household Welfare Survey (July – December 2024) - van Asselt, Joanna; Aung, Zin Wai (International Food Policy Research Institute, 2025)
The eighth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was conducted between October and December 2024. This round follows seven previous rounds carried out since December 2021 and reflects conditions during July – December 2024. This report presents updated insights on the conflict, climatic, service, and economic shocks households faced, as well as the coping mechanisms they employ in response. Security conditions were difficult throughout the recall period. Seventeen percent of households reported feeling insecure in their communities, while 19 percent reported low levels of trust. Crime and violence affected 17 percent and 8 percent of communities, respectively. Insecurity remained highest in Kayah, Chin, and Kachin, while Rakhine became more insecure and isolated. Lawlessness was also widespread: 17 percent of households reported gambling and 14 percent reported drug use in their communities, especially in urban areas. Thirty-five percent of households express concerns over conscription, particularly in urban centers like Yangon and Nay Pyi Taw, as well as states like Shan and Rakhine. Additionally, 13 percent of respondents reported feeling unsafe while moving around and carrying out everyday tasks in their communities, and 3 percent reported risks of kidnapping. Climatic shocks further compounded hardship. Nineteen percent of farming households experienced climatic shocks, with severe flooding reported by 45 percent of households in Kayin, 35 percent in Kayah, and 36 percent in Rakhine. Intense winds affected 14 percent of households in Chin. These events, like conflict, have contributed to the destruction of homes, infrastructure, and services, further deepening vulnerability. Service disruptions further undermine wellbeing. Among households connected to the national power grid, 78 percent experienced daily power cuts lasting at least one hour. In urban Rakhine, households face up to 16 hours of outages daily. Internet access was limited for 55 percent of households, with near-total internet blackouts in Rakhine and Kachin, and over 30 percent without access in Sagaing and Kayah. Although school enrollment and access to medical services rose modestly, it remained low in conflict-affected areas, especially in Rakhine. Economic pressures continue to mount. Food inflation reached 39 percent between September and December 2024. Prices rose sharply for leafy greens, potatoes, and chicken. Although rice prices also increased, their contribution to overall food inflation was the lowest since 2022, at 19 percent. Petrol prices rose by 7 percent in the quarter and 54 percent year-on-year. Non-food essentials such as soap (25 percent increase), paracetamol (26 percent), and toothpaste (128 percent) also saw steep price increases. Households have resorted to increasingly desperate measures to cope. By late 2024, only 20 percent of households had any cash savings or bank deposits – just 7 percent in Kayah. Migration remains a key strategy, with about 10 percent of households reporting a migrant in Q4 2024. Borrowing played a central role: 64 percent of loans came from informal sources like friends and relatives, and were largely used to cover food, health, and daily expenses. Amid these challenges, 52 percent of households reported giving to social services and one in four provided direct assistance to vulnerable neighbors or local food initiatives. However, if shocks continue to intensify, households’ ability to cope may further erode, leaving many without the resources needed to meet even basic needs.